Shear bond strength of the Iingually and buccally bonded brackets via three composite systems (Mustansiria Dental Journal, 2024)
This study aimed to determine and compare the shear bond strength of linguallybonded brackets via: Two—paste composite (Orthodontic Mix Bonding System), No —mix composite [Orthodontic Bonding System (No—mix)] and Light—cured composite( Transbond XT .)Thirty extracted upper first premolars for orthodontic request were used for thisinvestigation. The teeth were divided into three groups; each of which consisted of l0teeth. The lingual surface of the tooth used to evaluate the lingual bond strength andthe buccal surface of the same tooth utilized to evaluate the buccal bond strength. Foreach group of teeth investigated to determine the lingual and buccal bond shearstrength, using one type of composite system for each group .The lingually bonded and buccally bonded samples were subjected to shearforce using the universal compression testing machine apparatus. The lingual andbuccal shear bond strengths were recorded and converted into Mpa and the data werestatistically analyzed .The results showed the lingual shear bond strength insignilicantly less than thatof buccal shear bond strength regarding the Orthodontic Mix Bonding System andOrthodontic Bonding System (No—mix), and the lingual shear bond strength wassignificantly less than the buccal shear bond strength regarding Light—curedcomposite (Transbond XT), The lingual and buccal shear strengths of the bondedbracket via Orthodontic Mix Bonding System were the highest than the shear bondstrength of the other composite systems